Atlantic salmon (Salmo salar L., 1758) gut microbiota profile correlates with flesh pigmentation: cause or effect? - Nguyen, CDH; Gianluca Amoroso; Ventura, T; Minich, JJ; Elizur, A (2020)
In Tasmania (Australia), during the marine phase, it has been observed that flesh pigmentation significantly drops in summer, possibly due to high water temperatures (> 20 °C). Although this deleterious effect of summer temperatures has been ascertained, there is a lack of knowledge of the actual mechanisms behind the impaired uptake and/or loss of pigments in Atlantic salmon in a challenging environment. Since the microbial community in the fish intestine significantly changes in relation to the variations of water temperature, this study was conducted to assess how the gut microbiota profile also correlates with the flesh color during temperature fluctuation. We sampled 68 fish at three time points covering the end of summer to winter at a marine farm in Tasmania, Australia. Flesh color was examined in two ways: the average color throughout and the evenness of the color between different areas of the fillet. Using 16S rRNA sequencing of the v3–v4 region, we determined that water temperature corresponded to changes in the gut microbiome both with alpha diversity (Kruskal-Wallis tests P = 0.05) and beta diversity indices (PERMANOVA P = 0.001). Also, there was a significant correlation between the microbiota and the color of the fillet (PERMANOVA P = 0.016). There was a high abundance of Pseudoalteromonadaceae , Enterobacteriaceae , Microbacteriaceae , and Vibrionaceae in the pale individuals. Conversely, carotenoid-synthesizing bacteria families ( Bacillaceae , Mycoplasmataceae , Pseudomonas , Phyllobacteriaceae , and Comamonadaceae ) were found in higher abundance in individuals with darker flesh color.